Peran Strategi Komunikasi Pemasaran “Word of Mouth” Dalam Pengambilan Keputusan Konsumen - Dewi Shanti Nugrahani (FE Program Studi Manajemen, 2008)
A company needs to communicate its products to the community inorder to socialize its products so they will consume them. One of thestrategy is using marketing mix which is called word of mouth whichwill trigger the consumers to talk and promote furthermore they willrecommend its products to another consumers. In order that word ofmouth as communication marketing mix strategy can take part inconsumers making decision so the company must provide thesatisfaction toward its consumers for the establishment of positiveword of mouth.Key words: Marketing communication, word of mouth, consumersdecision